conceptual Provisions of compliance as a Form of Internal control in Economic Entities - Zh. A. Kevorkova; N. G. Sapozhnikova (Учёт. Анализ. Аудит, 2020)
The article is devoted to the issues of the organization of compliance as a type of internal control forms and the possibility of applying methodological approaches to it that are typical for the organization of the internal control system. The methodological basis and results of the study are based on the experience of management of international companies, on the organization of the compliance system, as well as on the results of a review of various sources of information regarding this issue. It is revealed that foreign practice allocates compliance to an independent structural division, whose employees are given the appropriate powers starting from consulting and training employees on compliance issues to conducting an internal investigation of fraudulent actions and participating in the identification and assessment of compliance risks of an economic entity. Recommendations that are made are based on the need to develop standards for an economic entity that meet international requirements for identifying and evaluating compliance risks associated with professional business conduct and monitoring them. The stages of development of compliance as a form of control are determined. The theoretical and practical significance of the study is to justify the application of existing practices of the compliance organization for the development of internal interaction rules, procedures, and decision-making process by an economic entity.